Gender Representation in The English Textbook for Grade Ninth in Indonesia - Wafda 'Aini; Elih Sutisna Yanto; Wahyudin Fitriyana (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2021)
This study aims to examine how different genders are represented in Indonesia's grade eight English textbooks. The primary goal of this research is to ascertain the various gender representations and how language and images are used in the English textbook